KERJASAMA INDONESIA DENGAN WHO (WORLD HEALTH ORGANIZATION) DALAM UPAYA MENANGGULANGI HIV AIDS DI INDONESIA TAHUN 2015-2017 : Array - Revlinur Rahmawati (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
The HIV AIDS case is a serious health problem or case, the case is not only in Indonesia but HIV AIDS has already become a health problem in various countries, and has become a global health problem, its spread is increasingly rapid in the world and in various countries. big. Through the Millennium Development Goals Program initiated by the United Nations, the United Nations has made HIV AIDS cases a focus to be tackled seriously. In tackling HIV AIDS in Indonesia, the government is working with WHO as a special agent for World Health. In writing this thesis, the aim that the writer wants to achieve or achieve is to find out what are the roles of WHO in overcoming the HIV AIDS problem in Indonesia to find out what factors are the obstacles in WHO's cooperation in tackling HIV / AIDS in Indonesia. The qualitative research writing method has meaning to understand the phenomena experienced by research subjects, for example a behavior, perception, motivation, action and so on. In an effort to tackle HIV AIDS in Indonesia, WHO has issued several programs, namely prevention, care and treatment programs, support for people living with HIV, the last is a research and evaluation program, with various efforts being made, but the number of HIV AIDS in Indonesia itself continues to increase every year, In this study the authors found obstacles in implementing the programs that have been attempted, including socio-cultural factors in Indonesia which are still high in stigma and discrimination against PLWHA, economic factors, especially in care and treatment programs, political factors, especially in services health.